Local engagement with the early English Reformation : Oxfordshire, 1520-1570 - Halliday, K (2006)
This thesis seeks, through the study of Oxfordshire, to explore how ordinary men and women negotiated religious change at a local level; to consider a wide and varied range of reactions to, and relationships with, religious alterations; and to investigate the dynamic between government and people in Tudor England. The first section of the thesis uses Oxfordshire's churchwardens' accounts to explore the process of the Reformation within the county's parish communities. Virtually all the money with which Oxfordshire's churchwardens funded their churches' operations had been raised voluntarily by their parish communities - meaning that, although the parishioners' attitudes did not dictate the actions of their churchwardens, they did much to determine the level of financial support that the wardens received for them. Accordingly, the analysis of Oxfordshire's churchwardens' accounts - and particularly the wardens' funding regimes - is enlightening as to how Oxfordshire's parish communities collectively responded to the alterations that the Reformation wrought in their churches' worship. The second section of the thesis explores the different ways in which individuals within communities such as those studied could, and did, engage critically with religious change. Oxfordshire was an outwardly 'conformist' county. Nonetheless, its commons engaged critically with religious change. Oxfordshire fostered both unlicensed evangelicalism and traditionalism throughout the Reformation period, with large numbers of the county's commonalty being in some way party to these. It was, however, unlicensed traditionalism which at times posed a very real threat to order within Oxfordshire. There was trouble at around the time of the Pilgrimage of Grace. The county was, moreover, the scene of two large-scale risings. In July 1549, several hundred of the Oxfordshire commons rebelled over matters of religion. Four years later, the county rose again in large number, this time under gentry leadership, in support of Mary Tudor's claim to the throne.